Islamisation: what it is not - Isahak, Aldila (2013)
This talk analyses the concept of Islamisation by presenting what does not reflect Islamisatio. Two models of Islamisation: al-Attas and al-Faruqi were presented and Cicero's concept of natural law was used to further refined the meaning of Islamisation. The conclusion was that IOHK is the correct concept to be adopted by IIUM.